Marketing and Income Analysis of Seaweed Farming Business - Menh Anh; Huy Perk Hanh (Newinera Publisher, 2021)
The purpose of this research is to conduct a marketing and revenue analysis of seaweed producers. This study takes a qualitative approach via the use of exploratory research techniques. This research included all farmers who grow seaweed. The Slovin formula was used to calculate the sample size, which was 40 heads of households. The sample is determined using a basic random sampling technique. While data gathering is accomplished via interviews, observation, and documentation. Farmers market their seaweed goods in two ways, first to middleman merchants, then to collectors, and lastly to inter-city traders. Second, farmers sell their produce to collectors, who subsequently distribute it to intercity merchants. The average revenue earned by seaweed growers. That is 6 USD –830 USD in a single manufacturing process, indicating that seaweed farming is lucrative and possible to expand, but that production expenses must be more efficiently used to achieve larger profits